The Legal Renewal of Malpractices by Medical Personnel Based on Restorative Justice - Hendradiana, Asep; Gunarto, Gunarto (Unissula, 2024)
The purpose of this research is to analyze and find regulations for handling suspected malpractice by medical personnel based on restorative justice. The research method uses empirical juridical; The results of the research indicate that the legal reform of malpractice carried out by medical personnel based on restorative justice is currently not in accordance with Restorative Justice, the current regulation of handling alleged malpractice by medical personnel lies in the substance of the law, namely the absence of nomenclature and rules for handling suspected malpractice by medical personnel in positive law. Indonesia. a legal structure that is still limited in its understanding and understanding by law enforcement officials. health law is not yet in accordance with the provisions of the health law, the legal culture of medical personnel whose legal understanding and awareness of health law is still not high, so that a just legal life in accordance with restorative justice has not been created. The value of justice in handling suspected malpractice provides balanced protection between medical personnel and patients, namely by providing services with noble and superior morals. health services, without stigma towards health workers and are fair and professional.